2004
DOI: 10.3141/1873-06
|View full text |Cite
|
Sign up to set email alerts
|

Short-Haul Rail Intermodal: Can It Compete with Trucks?

Abstract: Intermodal traffic, that is, truck trailers or ocean containers handled on special rail equipment, is the fastest-growing segment of rail traffic. Between 1990 and 2000, rail intermodal grew at an annual rate of 4.6%—much faster than rail carload freight, which grew at an annual rate of only 1.4%. However, during the same period, truck tonnage grew at an annual rate of 6.9%, and air cargo at a rate of 17.9%. The growing rail intermodal is expected to overtake coal as the single largest source of revenue for fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 1 publication
2
25
0
Order By: Relevance
“…It is notable that the share of drayage costs in the total costs is 30-40% (Spasovic and Morlok, 1993;FHWA, 1994;EC, 2000bEC, , 2001a. Resor and Blaze (2004) reported that drayage costs around a port region in the US account for more than 70% of the total costs when the transport distance is about 300 km. Barton et al (1999) surveyed experts and practitioners about the long-distance truck rate (b) in Minnesota, in the United States.…”
Section: Graphic Representation and Intermodal/truck-only Cost Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is notable that the share of drayage costs in the total costs is 30-40% (Spasovic and Morlok, 1993;FHWA, 1994;EC, 2000bEC, , 2001a. Resor and Blaze (2004) reported that drayage costs around a port region in the US account for more than 70% of the total costs when the transport distance is about 300 km. Barton et al (1999) surveyed experts and practitioners about the long-distance truck rate (b) in Minnesota, in the United States.…”
Section: Graphic Representation and Intermodal/truck-only Cost Reviewmentioning
confidence: 99%
“…UIRR (2000) distinguishes domestic and international intermodal transport: 550 km for domestic intermodal systems and 760 km for international intermodal systems (Bärthel and Woxenius, 2004). In North America, researchers estimate the break-even distance to be about 500 miles (800 km) (Transport Canada, 1996;Resor and Blaze, 2004;Lim and Thill, 2008) by using market observation. This survey/interview approach is simple, but the applicability of its results to other corridors/markets is limited.…”
Section: Conventional Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, gains are minimal along the Atlantic Seaboard and through most of the Southeast, over a depth from the coast line of 500-750 miles. This should not be a surprise since intermodal solutions are seldom competitive with trucking over shorter distances (Brown and Hatch, 2002;Resor and Blaze, 2004). Through the rest of the country, we observe a patchwork of medium to high accessibility gain areas.…”
Section: Accessibilities To Eastern Seaboard Portsmentioning
confidence: 84%
“…The road: rail trade-off in terms of cost efficiency is between 500 and 750 kms according to Resor et al (2004); in Canada, the distance is considered to be one-half day's driving distance by truck.…”
mentioning
confidence: 99%